2005
DOI: 10.1002/rcm.2223
|View full text |Cite
|
Sign up to set email alerts
|

Application of stable isotope labeled glutathione and rapid scanning mass spectrometers in detecting and characterizing reactive metabolites

Abstract: The formation of reactive metabolites from a number of compounds was studied in vitro using a mixture of non-labeled and stable isotope labeled glutathione (GSH) as a trapping agent. GSH was labeled by incorporating [1,2-(13)C(2),(15)N]glycine into the tripeptide to give an overall increase of 3 Da over the naturally occurring substance. Detection and characterization of reactive metabolites was greatly facilitated by using the data-dependent scanning features of the linear ion trap mass spectrometers to give … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
62
0

Year Published

2008
2008
2012
2012

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 78 publications
(63 citation statements)
references
References 18 publications
1
62
0
Order By: Relevance
“…7 In addition, stable-isotope labeled GSH has been used to improve the analytical efficiency of the assay. 8,9 Recently, highresolution mass spectrometry-based mass defect filtering 10 has been used to facilitate the screening and identification of GSH-trapped reactive metabolites. 11 All these techniques target a specific behavior or property of GSH adducts to facilitate their detection.…”
Section: Introductionmentioning
confidence: 99%
“…7 In addition, stable-isotope labeled GSH has been used to improve the analytical efficiency of the assay. 8,9 Recently, highresolution mass spectrometry-based mass defect filtering 10 has been used to facilitate the screening and identification of GSH-trapped reactive metabolites. 11 All these techniques target a specific behavior or property of GSH adducts to facilitate their detection.…”
Section: Introductionmentioning
confidence: 99%
“…These include neutral loss scanning mass spectrometry for a loss of the 129 Da pyroglutamic acid from endogenous glutathione adducts (93), or treatment of cells with glutathione ethyl ester (GEE) combined with precursor ion scanning of 300 m/z to detect the GEE linked analyte (94). In addition, treating cells with stable-isotope labeled GSH improves selective detection of glutathionylated molecules because they appear as a pair of light and heavy ions (95,96).…”
Section: Oxmrm: Quantitative Cysteine Oxidation Analysis By Mrm-multimentioning
confidence: 99%
“…Terminal acetylenes are well known to be mechanism-based CYP-inactivators (Testa & Jenner, 1981) and there is an increasing body of information suggesting that internal acetylenes can be activated by CYPs (Fontana et al, 2005;Foroozesh et al, 1997;Shimada et al, 2007) or even undergo uncatalyzed addition of glutathione Mutlib et al, 1999). Mutlib et al reported that incubation of MPEP with triple-labeled glutathione gave compounds with molecular weights and fragmentations consistent with both activated and unactivated addition of GSH to the alkyne (Mutlib et al, 2005). These events are potential sources for hepatic or idiosyncratic toxicity.…”
Section: Allosteric Modulators and Radiotracers For Mglur5mentioning
confidence: 99%